Diet of the elderly according to the place of residence - Troncoso Pantoja, Claudia (2017)
The exponential growth of the elderly population nowadays demands to take a closer look at the diet and eating behavior of this age group, as a way of improving their health and quality of life, which is influenced, among other factors, by their place of residence. This article delves into the diet of older adults according to their place of residence: long-term nursing homes or other type of residential facility. The eating behavior of institutionalized elderly people is featured by eating at least three scheduled meals with menus showing inappropriate nutritional benefits, which do not adequately cover the nutritional requirements of the aged user and, along with other factors, favor malnutrition caused by dietary deficiency. Non-institutionalized people also tend to eat three scheduled meals with inadequate food quality. It can be considered that elderly people’s diet, regardless of their place of residence, is not appropriate for the respective age group.